Phyto-ecological distribution patterns and identification of alien invasive indicator species in relation to edaphic factors from semi-arid region. (April 2023) - Waheed, Muhammad; Marifatul Haq, Shiekh; Arshad, Fahim; Bussmann, Rainer W.; Ali, Hayssam M.; Siddiqui, Manzer H.
Highlights: Predicting the ecosystems at risk of invasion from AIPs. Key indicators AIPs were Parthenium hysterophorus, Prosopis juliflora, and a few more. Appropriate Strategy for spatial planning Abstract: The evaluation of alien invasive plants (AIPs) environmental and ecological distribution patterns can provide important data as well as a theoretical approach for management methods such as invasion prevention, eradication, and control of established AIPs, and recognition of ecosystems at high threat of invasion. Twenty 100 m 2 transects were randomly established at each of the ten sample sites to collect data on the impact of edaphic properties on the spread of alien species in the semi-arid region. After computing the Important Value Index for each recorded species, ordination and indicator species analyses were carried out. In the study area, 104 alien plants from 30 families and 72 genera were found. Poaceae was the largest family, with 18 taxa (17%), followed by Fabaceae (14 taxa; 13%) and Asteraceae (11 taxa; 10%). Herbs made up 51% of these species, grasses 17%, and shrubs 12%. In terms of life form, Therophytes (56%) were dominant, followed by Chamaephytes (12%). The leaf size spectrum of alien plants was dominated by microphylls (48%), followed by mesophylls (23%), and nanophylls (20%). The CCA ordination analysis clearly showed that environmental variables like pH, moisture and soil texture (silt, sand, and clay) significantly (p ≤ 0.002) influenced how species are distributed in the region. In total, twenty indicator alien species were detected across five different semi-arid ecosystems. Parthenium hysterophorus recorded from all ecotypes except wetland with highest IVI from agroecosystem. Prosopis juliflora was observed in urban ecosystems, while Stellaria media was in both agroecosystems and forests, and Lantana camara was only observed in forests. Our findings reveal patterns and processes of alien invasive plant in different ecotypes, but only remediation and continuous monitoring might affect the situation in the near future. In this regard, the baseline data gathered during the current study would be significant in guiding future scientific monitoring of such ecological changes, as well as in landscape ecology management and planning.